Can the behavioral agency model refine a standard agency theory? - Muhammad Masyhuri (Journal of Enterprise and Development (JED), 2024)
Purpose — The existence of agency problems is widely recognized in various academic fields. Nevertheless, as argued by many scholars, agency theory has obvious shortcomings both theoretically and empirically. The aim of this study is to analyze and compare the conventional Standard Agency Theory (SAT) and the Behavioral Agency Model (BAM) as a refined framework of an agency model.Method — The methods used for this study were descriptive analysis, involving the review and comparison of the work of Wiseman & Gomez-Mejia (1998) and Pepper & Gore (2015). The technique employed and proposed for this method is to analyze and compare the relevant elements between SAT and BAM.Result — It is found that BAM can provide a better framework for modifying and understanding such agency problems in organizations, particularly in terms of human factors, organization, and information assumptions that are considered to balance the roles of the principal and the agent as actors in the organization.Contribution  — This study contributes to the body of knowledge by refining the old and conventional standard agency theory (SAT) and introducing BAM as a new concept. BAM sheds light not only on the roles of actors and organizations but also on the application of a behavioral economics approach to provide a robust and rigorous method for analyzing "agency problems" in organizations, especially in private business families around the world.